Relationship of Heredity, Environment, and Human Freedom in Islamic Education - Muslihudin; Nurhuda, Abid; Rumani (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2023)
Social facts prove the problem of education when each individual prioritizes his selfish nature under the pretext of freedom of expression. In addition, many educators still use one method in dealing with various problems of their students. Even though students have different heredity. In fact, in practice, many educators consider classroom learning to be a stage to show off their intelligence in front of students so that students only act as spectators. Indirectly, educators have created a monotonous environment that does not support student self-development. The purpose of this research is to find out the nature of heredity, environment, and human freedom in self-development and their relationship in Islamic education. This research includes qualitative research using library research methods. The results of this study state that heredity, environment, and human freedom are integral parts that cannot be separated in individual development. Heredity or intrinsic potential is a factor that needs to be developed through the encouragement of good environmental facilities. Then, human freedom supports each individual to act and think creatively through education. Therefore, through this research, the authors offer the concept of a democratic school which is the result of the relationship between heredity, the environment, and the freedom of each individual.